Balancing heritage preservation and tourism development: a case study of Non Nuoc Cao Bang UNESCO Global Geopark, Vietnam - Pham, Huong Giang; Kieu, Quoc Lap (Bulletin of Geography. Socio-economic Series, 2025)
This study assesses the current state of heritage conservation at the Non Nuoc Cao Bang UNESCO Global Geopark (Vietnam) and examines the impact of tourism on historical and cultural sites. Using a survey of 500 respondents, including local community members, tourists and heritage experts, combined with field data analysis and GIS technology, the research reveals that, although public awareness of heritage values is relatively high (74.3%), the effectiveness of conservation efforts remains limited, with only 39.3% of respondents expressing satisfaction with current measures. The adoption of digital technology in conservation is also low (34.6%). Tourism in the geopark has grown at an average annual rate of 12.4%, but this increase has led to the degradation of 30.6% of heritage sites. The study identifies virtual reality (VR), mobile applications and integrated conservation-education models as promising solutions to improve heritage preservation and management. ...